What if Moros acted like Catalans?. IN Commentary [column] - Lanto, Macabangkit B. (Philippine Daily Inquirer, 2017)
To the mujahideen-autonomists: Armed struggle is not the only means to achieve your dream of a Moro homeland. The alternatives are varied.